Optimalisasi Ketercapaian Pajak Bumi Dan Bangunan Perdesaan Perkotaan (PBB-P2) Dalam Meningkatkan Pendapatan Asli Daerah Kota Medan - Topanta Kaban; Latersia Br. Gurusinga; Hermawan Sutanto (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2025)
This study aims to analyze the optimization of the achievement of Rural and Urban Land and Building Tax (PBB-P2) in increasing the Local Own-Source Revenue (PAD) of Medan City. In the context of fiscal decentralization, PBB-P2 is a crucial instrument that local governments can utilize to finance development and enhance fiscal independence. This research employs a qualitative descriptive approach, using data collection techniques such as literature review, observation, and documentation of PBB-P2 realization and target data in Medan City during the period 2021–2023. The results indicate that despite the significant tax potential, the realization of PBB-P2 revenue tends to decline and has not met the expected targets. This is mainly due to inaccurate tax object data, low taxpayer awareness, and weak administrative and collection systems. To address these issues, optimization strategies are needed, including updating the tax database, educating the public, improving human resource capacity, and implementing information technology systems that support tax administration efficiency. The optimization of PBB-P2 collection is expected to sustainably increase Medan City’s PAD and strengthen public service delivery in the future.